Pelatihan Pemanfaatan AI untuk Efisiensi Dokumen dan Penulisan Laporan bagi Pegawai SPNF SKB Majene - Arifin, Sartika; Aprisal; Hertanti, Alfiraminta (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
This community service activity (PkM) is in the form of training to use of AI for document efficiency and report writing for SPNF SKb Kab. Majene employees, which was held for 8 meetings, namely from July to August 2025. AI training activities for document and report preparation were carried out to address the challenges of rapid technological developments. This training activity consists of three stages, namely: 1) the observation stage, 2) the implementation stage consisting of module preparation and training implementation, and 3) the evaluation stage. The materials presented in this training are Ms. Office (Ms. Word and Excel) for document management, the use of AI such as ChatGPT and Grammarly for document and report preparation, and Canva for document design. The results of the AI ​​​​utilization training received a good response from the training participants. Furthermore, the results of the AI ​​​​training showed an increase in the competence of SPNF SKB Kab. Majene employees in preparing reports and other official documents. Documents prepared using AI are more credible and efficient in terms of time.